Emotional intelligence and teachers’ performance based on their professional competencies in the Educative Institution Mentes Brillantes– Trujillo, 2014 - Espinoza Rodríguez, Olenka Ana Catherine (2015)
This research had as general objective to determine the relation between emotional intelligence and the teachers’ performance based on their professional competencies in the Educative Institution Mentes Brillantes - Trujillo, 2014. It revalidates a referential framework about emotional intelligence and the relation with teachers’ performance based on their professional competencies. The observational method was applied. Its population was made up by twenty teachers from the institution mentioned above. It was used the technique of test for the first variable whose instrument was the emotional inventory of Bar On Ice and the survey for the second variable. This research identified the emotional intelligence levels of teachers and it established the teacher’s performance levels based on their professional competences. In both cases it denoted an average level respectively. It considered only certain competences although in the literature there are several competences that can be applied to different activities and its corresponding performance. Finally, it was analyzed and determined the relation between the two variables with Pearson and Spearman correlation where it was found that the correlation between the interpersonal component and influence and cognitive competence. The research results allow to solve problems such as lack of empathy, limited emotions control in some cases, among other factors do not allow to reach a high level of performance trough competences.